Symptoms, functioning and coping strategies in individuals with schizophrenia spectrum disorders who do not take antipsychotic medication: a comparative interview study. Issue 10 (7th June 2016) - Jung, E.; Wiesjahn, M.; Wendt, H.; Bock, T.; Rief, W.; Lincoln, T. M.
Abstract : Background: A considerable proportion of people with schizophrenia spectrum disorders do not take antipsychotic medication but seem to be functioning well. However, little is known about this group. To test the assumption that absence of medication is compensated for by more effective coping and increased social support, this study compared symptoms, functioning, coping strategies and social support in non-medicated and medicated individuals with schizophrenia spectrum disorders. Method: In all, 48 participants with a DSM-IV schizophrenia spectrum disorder who were taking ( n = 25) or not taking antipsychotic medication ( n = 23) were included. Assessment consisted of self-ratings of symptoms, symptom-related distress and social support combined with a semi-structured interview that assessed general and social functioning, subjective evaluation of symptoms and coping strategies. Results: Symptom severity and distress did not differ between the groups. However, the non-medicated participants had significantly higher levels of general functioning than medicated participants and a longer duration of being non-medicated was significantly associated with a higher level of general functioning. In contrast to the hypotheses, not taking medication was not associated with more effective coping strategies or with higher levels of social support. Medicated participants more frequently reported the use of professional help as a coping strategy. Conclusions: Our results corroborate previous studies finding improved functioning in individuals with schizophrenia spectrum disorders who do not take medication compared with those who take medication, but do not support the notion that this difference is explicable by better coping or higher levels of social support. Alternative explanations and avenues for research are discussed.